Transformasi strategi kualiti dan penjenamaan penerbitan: satu kajian terhadap Buku Fixi / Mohd Syuhaidi Abu Bakar and Siti Nor Fazira Jono - Abu Bakar, Mohd Syuhaidi; Jono, Siti Nor Fazira (2019)
Quality transformation strategy and publishing house branding strategy impacts all aspects of business. The objectives of this study were to investigate the quality transformation strategy and publishing house branding strategy of Buku Fixi. Qualitatively, this study has interviewed 10 informants consists of Buku Fixi's readers, writers and the management itself. Discussions were transcribed verbatim and imported into ATLAS.ti 4.2 software program. It was found that Buku Fixi has consistently upgrade their storytelling, language style and genre of a work as a part of their quality transformation strategy. In terms of publishing house branding strategy, Buku Fixi has decided on an elevated promotion via social media, a fixed logo and the rule of using online one-word title for each publication. It can be concluded that any publishing house needs to effectively manage its own brand as well as that of its authors and products, and social media seem to be a tool that will increase in importance for marketing and branding. Buku Fixi is one of those publishing companies that set advanced content and formats as an important goal.